Current aspects of diagnosis and treatment of surface thrombosis of the leg - Stücker, M.; Reich-Schupke, S. (Phlebologie, 2018)
The term „superficial venous thrombosis” (SVT) is more suitable to characterize the impact of the underlying disease instead of the old term „thrombophlebitis”, since 25% of the patients have additional thrombembolic complications as a deep venous thrombosis or pulmonary embolism. If SVT is found in varicose veins, these veins should be therapied after the healing of the acute thrombosis. SVT independent of varicose veins are often seen in patients with malignancies, thrombophilia and other risk factors oft he deep vein thrombosis. Although the diagnosis of SVT could be made by clinical findings a creful duplex is essential to detect the extend of the thrombus and the exact location – perhaps with progress into the deep venous system. The complete venous system of both legs should be examined as the main reason for the SVT is hypercoagulability. Therefore, concomitant deep venous thrombosis can be detected on the same but also on the other leg. The therapy of SVT depends on the affected vein: 1) In small tributary veins cooling, compression therapy and nonsteroidal antiinflammatory drugs as well as a small inzision and expression of the thrombus are sufficient. 2) In SVT of saphenous veins and larger tributaries with a length of 5cm or more, anticoagulation in prophylactic dose for 4–6 weeks and compression treatment for 3 months is recommended. In patients with risk factors like cancer, autoimmune disease or SVT in non-varicose veins, thromboembolic complications are often seen after the end of the 6-weeks anticoagulation. In these patients special instructions are helpful. 3) A SVT nearby (<3cm) the crossing to the deep venous system or with extend into the deep venous system should be treated like a deep venous thrombosis.
Keywords: Superficial venous thrombosis; heparin; compression; fondaparinux; rivaroxaban; duplex